Comparative analysis of the mucosal and shell microbiota of Trachemys scripta elegans across multiple urban freshwater habitats - Mariangel Correa Orellana; Coleman Odom; Anastasia Kuzmina; Jessica Urias-Quiroz; Laura Arias; Alyssa Kwiatowski; Georgina Aitolo; Patrick Martin; Colby Seitze; Meredith Winfield; Aspen Frisch; Jenna Tansiongco; et al. (PLoS ONE, 2026)
Turtles harbor diverse microbial communities that influence their health, ecology, and interactions with the environment. While sea turtle microbiomes have received growing attention, the microbial communities associated with freshwater turtles, particularly the widely distributed and invasive red-eared slider ( Trachemys scripta elegans ), remain understudied. Here, we used 16S rRNA gene sequencing to characterize the microbiomes of 42 red-eared sliders across four urban aquatic habitats in Austin, Texas, USA, sampling five body locations: carapace, plastron, skin, oral cavity, and cloaca. A total of 142 samples yielded 20,160 Amplicon Sequence Variants (ASVs), with community composition most strongly structured by body location, but also by geographic habitat. External surfaces (carapace, plastron, skin) were dominated by Cyanobacteria, Proteobacteria, and Deinococcota, while oral and cloacal samples exhibited higher proportions of Bacteroidota and site-specific variation. Alpha diversity differed significantly across habitats of origins but not across body locations, while beta diversity analyses revealed distinct microbial profiles among body regions. Notably, we report the first characterization of the oral microbiome in red-eared sliders, which was dominated by Proteobacteria and Deinococcota—patterns consistent with other reptiles. These findings shed light on microbial communities in invasive freshwater turtles and emphasize the need for broader microbial surveillance in urban aquatic ecosystems where wildlife and humans frequently interact.